Subjects, topics and the accusative case alternation in Finnish. A discourse-related “split” account of the Subject function - Ylinärä, Elina; Frascarelli, Mara (Lingua, 2021)
•Topics […] can occupy a (possibly) unique Topic position above the Subject. (lines 181–182)•An ‘agreeing Subject’ moves from Spec,TP to Spec,SubjP, qualifies as a full Subject. (lines 820–821)•An expletive that is merged in Spec,SubjP exclusively serves for the EPP requirement. (line 826)•the Subject function is realized in two distinct projections in the high IP-zone. (lines 1206–1207)•only ‘full’ Subjects can assign the -n ending Accusative Case to their complement. (lines 1215–1216). This article investigates the morpho-syntactic and discourse properties of preverbal constituents in Finnish, providing a new interpretation of the distinction between Subjects and Topics, as well as an explanation for the Case forms that characterize the Object realization in this language. Based on a cartographic approach to Finnish clause structure, evidence is provided for a functional ‘separation’ between the evaluation of the EPP feature and the domain of Nominative Case assignment. Specifically, a functional ‘split’ is proposed in the high IP-zone between the TP projection, where Nominative Case is checked by the sentential Subject triggering verb agreement, and the SubjP position, dedicated to the EPP requirement and hosting the Subject of predication. Based on this distinction, preverbal constituents only qualify as ‘full Subjects’ if they pass through both Spec positions. Specific consequences apply to Subject agreement and the realization of Accusative Case when these projections host different constituents (e.g., necessive, existential and passive clauses). This split account can also provide a distinction between the Subject of predication (in the IP-zone) and a Topic (in the C-domain), showing that not any preverbal constituent can be a Subject, while any constituent can be topicalized, with specific discourse functions and language-specific restrictions.